On Maxwell’s, Klein’s and Wieghardt’s Stress Functions for Discontinuous Media - Rieder, G. (Engineering Transactions, 1979)
When working on reciprocal diagrams, later named after Cremona, Maxwell noticed that the statics of plane frames in the absence of external forces can be represented by a piecewise linear, discontinuous stress function of Airy type. Klein and Wieghardt visualized this by the "stress surface", portraying Airy’s function degenerating into a piecewise plane "facet surface". In 1920 Funk proposed its practical application in connection with Castigliano’s principle. Following lines of analogy proposed by Kron, Kardestuncer and others, the static quantities defining each "facet" prove to be analogous to the circular currents of electrical networks in the same sense as displacement and rotation of a joint in a frame are analogous to the potential of an electric network node. Generalizations into space are discussed.